Pemberdayaan Masyarakat Dalam Pengelolaan Limbah Organik di Desa Krimun Indramayu - Hilmi Hilmansyah; Murni; Masniar; Nirwana Nurdjan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
Community empowerment in the context of organic waste management in Krimun Village, Indramayu. The main focus is understanding how participatory approaches can be used to increase community awareness and involvement in organic waste management. Community participation in organic waste management and evaluating the effectiveness of various policies and programs that have been implemented. Empowerment results show that through training, counseling and development of supporting infrastructure, the people of Crimen Village can be more actively involved in collecting and processing organic waste. Community empowerment is implemented through the formation of small groups responsible for managing organic waste at the household level. This program not only provides environmental benefits, but also has a positive impact on community welfare through economic involvement in compost production and related activities. The results of empowerment using this patricipatory approach provide insight for local governments, waste management institutions and the general public regarding empowerment strategies that can be adopted to achieve sustainable organic waste management at the village level.